The suspicion - Applegate, Katherine (New York : Scholastic, 1998)
The Yeerks are not the only invaders of Earth. Meet the new enemy: the Helmacrons. Cassie finds their miniature spaceship and donates it to a toy drive. Big mistake. The Helmacrons are tiny, but they're far from helpless. They have the technology to shrink other creatures to their size. And until they get their spaceship back, they're taking hostages. The Animorphs must find a way to send these pests back into space--before it's too late.
O
"An Apple paperback."
640
O
Keywords: Science fiction; Metamorphosis -- Juvenile fiction; Children's stories; Science fiction